Missed Opportunities: Healthcare Encounters Prior to Sudden Unexpected Infant Death - Salada, Katherine O.; Badke, Colleen M. (Frontiers in Pediatrics, 2022)
Introduction: Sudden unexpected infant death (SUID) is the leading cause of death in children 28 days to 1 year of age. The study aim was to identify opportunities for healthcare professionals to provide families with education on sleep and prevention of SUID. Methods: We performed a retrospective chart review of SUID infants over 10 years (12/2010–12/2020). The study included patients 0-12 months who presented to single institution with SUID (including asphyxia, suffocation, and SIDS). Baseline descriptive characteristics, sleep patterns (location, position, co-sleeping, presence of pillows/blankets), and prior healthcare encounters (type, duration, frequency, timing) were described. Results: 35 infants met inclusion criteria. 23% of families routinely practiced unsafe sleep, while 63% practiced unsafe sleep at the time of SUID. All unsafe sleep behaviors increased during the SUID event compared to routine, including inappropriate location (60%), co-sleeping (46%), and inappropriate position (37%) at the time of SUID. There were 54 total healthcare encounters (mean 1.5 per patient + 2.1) prior to SUID. Primary care physicians (57%) and NICU (29%) were the most frequent prior healthcare encounters, however visits spanned multiple specialties. 26% had a healthcare encounter within 7 days of their death. Discussion: We demonstrated the frequency and variability in healthcare encounters among SUID infants prior to their death. Majority of infants had prior healthcare encounters, with 26% seen by healthcare professionals within 7 days of their death. These results highlight the important role healthcare professionals across all specialties have the potential to play in educating families about safe sleep and SUID.